How urban renewal affects the sustainable development of public spaces: trends, challenges, and opportunities - Xia, Jun; Zhao, Ziyou; Chen, Lingqiong; Sun, Yazhen (Frontiers in Environmental Science, 2024)
The process of urbanization has spurred economic growth and social challenges, necessitating research on public spaces in urban renewal to optimize design, enhance functionality, promote sustainable urban development, and improve residents’ quality of life. However, existing studies lack in-depth discussions on development trends and research focal points. This study addresses the gap in existing literature, by conducting a bibliometric analysis using data from the Web of Science Core Collection database from 1 January 2000, to 1 April 2024. Using visualization tools such as VOSviewer and CiteSpace, the study examines publication trends, collaborative networks among countries, institutions, and authors, co-citation relationships among key journals and articles, and emerging research hotspots through keyword analysis. A total of 393 papers were analyzed, with China contributing the highest number (65), followed by the United States (51). Leading contributors include Zazzi Michele and Anguelovski Isabelle. The top three journals for publications are Sustainability, Cities, and Land. Key research trends highlight themes such as space syntax, nature-based solutions, and sustainable transportation. These findings have significant implications for urban planning and policy, suggesting that future urban development strategies should increasingly incorporate sustainable design practices and nature-based solutions to address both environmental and social challenges. By identifying global research trends and highlighting future challenges, this study provides a comprehensive overview that will help policymakers and practitioners in urban planning align their efforts with cutting-edge research and emerging best practices for more sustainable and resilient cities.